If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3-4x=7x-1
We move all terms to the left:
3-4x-(7x-1)=0
We get rid of parentheses
-4x-7x+1+3=0
We add all the numbers together, and all the variables
-11x+4=0
We move all terms containing x to the left, all other terms to the right
-11x=-4
x=-4/-11
x=4/11
| 5x-12=3x+13 | | 16-4u=0 | | 5(x-3)=2(2x+6) | | 5(4x/3)=135 | | .06(n-450)=105 | | 70y-6=7 | | 5(11x-)=155 | | f(-3)=-3^2-5(-3)+36 | | 5(11x-)=-28 | | 5x-4=4x-10 | | 3x-11+5x/2=0 | | 6x-3=9x-24 | | 10x=-32-6 | | 7(4x+3)=27x+37 | | 6x-11-7=6(x-3) | | 3−7⋅3+4x=-18 | | 2x+1.9=4.1x+1.27 | | 3.6x-8.4=9.6 | | 2x+2(7-3x)=21 | | F(x)=-2x-5x+7 | | 3x^2+33x-8.1=0 | | 20/13=60/d | | -3x-9=5x+7 | | 12x-48=3x-3 | | 3m+7=97 | | 12x-48=3x-4 | | 7x-4=4x+5= | | x+8/3=x+2/3 | | 7×4=4x+5 | | 2+6x=-2x+10 | | 3x/5+7=2x/6+9 | | 2+6x=2x+10 |